Mechanisms of DNA damage induced by morin, an inhibitor of amyloid β-peptide aggregation. (2nd January 2019) - Mori, Yurie; Kato, Shinya; Fujisawa, Yutaka; Ohnishi, Shiho; Hiraku, Yusuke; Kawanishi, Shosuke; Murata, Mariko; Oikawa, Shinji
Abstract: Morin is a potential inhibitor of amyloid β-peptide aggregation. This aggregation is involved in the pathogenesis of Alzheimer's disease. Meanwhile, morin has been found to be mutagenic and exhibits peroxidation of membrane lipids concurrent with DNA strand breaks in the presence of metal ions. To clarify a molecular mechanism of morin-induced DNA damage, we examined the DNA damage and its site specificity on 32 P-5′-end-labeled human DNA fragments treated with morin plus Cu(II). The formation of 8-oxo-7, 8-dihydro-2′-deoxyguanosine (8-oxodG), an indicator of oxidative DNA damage, was also determined in calf thymus DNA treated with morin plus Cu(II). Morin-induced DNA strand breaks and base modification in the presence of Cu(II) were dose dependent. Morin plus Cu(II) caused piperidine-labile lesions preferentially at thymine and guanine residues. The DNA damage was inhibited by methional, catalase and Cu(I)-chelator bathocuproine. The typical OH scavengers ethanol, mannitol and sodium formate showed no inhibitory effect on DNA damage induced by morin plus Cu(II). When superoxide dismutase was added to the solution, DNA damage was not inhibited. In addition, morin plus Cu(II) increased 8-oxodG formation in calf thymus DNA fragments. We conclude that morin undergoes autoxidation in the presence of Cu(II) via a Cu(I)/Cu(II) redox cycle and H2 O2 generation to produce Cu(I)-hydroperoxide, which causes oxidative DNA damage.